The emotional enhancement of memory: encoding and retrieval effects - Chipchase, Susan Y. (2010)
The influence of emotion on memory and the role of encoding and retrieval effects were examined in a series of 10 experiments. Retrieval effects were examined in the first 3 experiments by investigating the success of different memory retrieval strategies. Positive emotional enhancement of recognition was found in traditional two-alternative forced-choice recognition and a task which encouraged a nonanalytic retrieval strategy. No emotional enhancement of memory was found in a task which encouraged an analytic retrieval strategy or when a Remember / Know / Guess judgement followed recognition. The paradigm was adapted to a within-participants design but emotional enhancements of recognition were no longer found. The next 7 experiments explored encoding effects with a paradigm investigating visual specificity of memory. Participants identified whether pictures were Same / Similar / New (SSN) in comparison to those shown at study. The findings from the SSN and Remember / Know / New paradigm were compared, with negative emotional enhancement of memory found in both. Negative and positive emotional enhancement of memory for specific visual details was found, with a central-peripheral trade-off in memory with negative emotion when objects were presented on congruent neutral backgrounds. Eye movements were recorded at encoding to examine attentional effects. Attentional narrowing was found on scenes with a negative object but no attentional effects were found with positive emotion. In the last 3 experiments associative memory, implicit memory, distinctiveness of emotional stimuli and warnings of emotion were measured and manipulated but could not account for the memory effects. Surprisingly, the emotional memory effects remained even when stimuli were blocked into emotional groups radically altering the distribution of visual attention. The implications of the results for choice of experimental stimuli, task instructions in experimental paradigms and the memory processes of encoding and retrieval are discussed.